2021
DOI: 10.21037/tau-20-1226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-sodium diet on lithogenesis in a rat experimental model of calcium oxalate stones

Abstract: Background: This study aimed to investigate the effects of a high-and low-sodium diets on lithogenesis in a rat experimental model of calcium oxalate stones.Methods: Twenty male Wistar rats were randomly divided into four groups; group A: 4% NaCl+1% ethylene glycol (EG); group B: 8% NaCl+1% EG; group C: 8% NaCl+normal drinking-water; group D: 1% EG +normal diet. All rats were sacrificed 4 weeks later, and blood samples were collected from the heart.The kidneys were collected for Von Kossa staining to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…High dietary sodium ingestion is accompanied by increased urinary calcium excretion [ 78 , 79 ] and CaOx crystal deposition in the kidney [ 80 , 81 ]. In pediatric patients, higher dietary sodium intake is also associated with calcium urolithiasis [ 82 ].…”
Section: Strategies To Prevent Ksdmentioning
confidence: 99%
“…High dietary sodium ingestion is accompanied by increased urinary calcium excretion [ 78 , 79 ] and CaOx crystal deposition in the kidney [ 80 , 81 ]. In pediatric patients, higher dietary sodium intake is also associated with calcium urolithiasis [ 82 ].…”
Section: Strategies To Prevent Ksdmentioning
confidence: 99%
“…A high or low sodium concentration is a regulator of metabolic changes in patients with kidney stones. Sakhaee et al found that high sodium intake increased calcium excretion and urinary pH and decreased citric acid excretion (144,145). In addition, high sodium intake may reduce calcium reabsorption by the renal tubules, resulting in increased urinary calcium and stone formation (146).…”
Section: Other Metabolic Changesmentioning
confidence: 99%